Myanmar's 'civilian' government : one month on - Kyaw, San Wai (2012)
One month into office, President Thein Sein’s government has been sending mixed signals on reform. Many challenges remain for the fledgling government. How should ASEAN respond to this “new” face of the ruling elite in Myanmar?